PERIARTICULAR CYSTS OF FACET JOINTS: ETIOPATHOGENESIS, DIAGNOSIS, METHODS OF SURGICAL TREATMENT. A CLINICAL EXAMPLE - V. A. Byvaltsev; V. A. Sorokovikov; A. A. Kalinin; A. K. Okoneshnikova (Acta Biomedica Scientifica, 2018)
Background. Periarticular cysts (PC) of facet joints is a rare pathology in neurosurgical practice. The concept of PC is applicable for all cysts that are located either pararticularly in the region of facet joints, or start from them.Material and methods. A systematic search was performed in medical databases: Medline, RINC, EMedicine, UMKB, Pubmed on the relevant topic in Russian and English. The search query includes  words: arcuate joint, periarticular cyst, clinic, diagnosis, surgical  treatment. One of the significant factors of PC development is the  instability of the vertebralmotor segment of both degenerative and post-traumatic character.Results. The result of the literature review was the writing of a clinical lecture, the current state of the issue of etiopathogenesis, diagnosis and management of patients with  periarticular cysts of facet joints was studied. The article gives a  clinical example of surgical treatment of a patient with a periarticular cyst at the level of LIV-LV on the right.Conclusion. Periarticular cysts of facet joints are one of the factors of compression of cauda equina roots, with surgical treatment being  a radical and effective way of treatment. A detailed study of this  pathology is a promising direction in spinal neurosurgery. Further  research is required on comparative analysis of clinical and  instrumental efficacy of various methods of surgical treatment of periarticular cysts of facet joints.